Strengthening the Efficiency of Parliamentary Oversight Bodies to Enhance Anti-Corruption Control, Transparency, Political Accountability, and Responsibility - Tony Duba; Thakaramahlaha Lehohla (Business Ethics and Leadership)

(untitled)
The extent of corruption in South Africa has been fast catching up to that of the world. It is public knowledge that the past two decades have seen several government initiatives aimed at combating corruption, and none of these seems adequate to rid South Africa of the plague of corruption and severe corruption at high levels of government. The parliament has a primary role to play, which involves exercising that role over government departments and ensuring that public resources are used for their intended purpose, and Chapter 9 institutions must play their primary role. The researchers dissect the role of parliamentary oversight institutions through the Standing Committee on Public Accounts and how it can be strengthened by working as a trilogy of parliamentary oversight institutions together with Chapter 9 institutions in conjunction with the Special Investigation Unit and Directorate of Priority Crime Investigation, to contribute to political and administrative accountability. The research was conducted in South Africa in 2025, comprising 30 participants: current or former parliamentary presiding officers, former and current SCOPA chairpersons; the current and former parliamentary oversight senior officials, current and former chapter 9 institutions heads or managers relevant to the study and current and former members of justice, crime prevention and security cluster services officers with intimate knowledge of parliamentary oversight work. The questionnaire consisted of open-ended questions and qualitative interviews that raised issues of accountability involving a trilogy of oversight institutions in South Africa and their lack of capacity to arrest the scourge of corruption in South Africa. The developed theoretical framework for improving the performance of the trilogy of parliamentary oversight institutions in South Africa is based on the paradigm and conditional/consequential framework of Corbin and Strauss (2008). The methodology applied was a qualitative research approach based on semi-structured and desktop methods of data collection, and the comparative analysis method assists the main goal of aiding a researcher with the focused and systematic generation of theoretical frameworks from data. The research entailed qualitative interviews being held. The processing of the results comprised narratives expressing the general view of participants as well as graphical representation based on the data collected. The relationship between government and parliament has conventionally been a vital connection within democracies. Political scientists and accountants argue that parliament is essential in safeguarding liberty. The general question addressed by this study is how the trilogy of oversight institutions can work together to improve accountability through developing a theoretical framework, with the general objective of creating a theoretical framework for improving accountability through a trilogy of oversight institutions. In terms of prospects opened by this research, it precipitates the need to investigate the reasons why serious matters need to be dealt with and what remedies would strengthen oversight in terms of new legislation and institutionalized collaborative effort between Chapter 9 institutions and parliamentary oversight.